Measuring the Community's Legal Awareness of Land Rights Around Lake Limboto - Paramitha Poetri Herliono (Estudiante Law Journal, 2019)
Abstract: This study is intended to determine the level of legal awareness of the community around Lake Limboto towards land rights; This study uses empirical legal research methods, where facts in the field are used as data in measuring and determining the truth in research. The data source used is the primary data source as the main data and secondary data sources as supporting data consisting of documents and scientific works related to the issues being discussed. The sample (respondents) used in this study were people in the Dembe I Village. The results showed that first, the level of public awareness in Dembe I Village who lives on the banks (coastal) of Lake Limboto is still low. Second, The cause of the low level of public awareness is the lack of knowledge about the management of land rights.Keywords: Legal Awareness; Land Rights; Border.